Not Part of the Temporal Lobe, but Still of Importance? Substantia Nigra and Subthalamic Nucleus in Epilepsy - Bröer, Sonja (Frontiers in Systems Neuroscience, 2020)
The most researched brain region in epilepsy research is the temporal lobe, and more specifically, the hippocampus. However, numerous other brain regions play a pivotal role in seizure circuitry and secondary generalization of epileptic activity: The substantia nigra pars reticulata (SNr) and its direct input structure, the subthalamic nucleus (STN), are considered seizure gating nuclei. There is ample evidence that direct inhibition of the SNr is capable of suppressing various seizure types in experimental models. Similarly, inhibition via its monosynaptic glutamatergic input, the STN, can decrease seizure susceptibility as well. This review will focus on therapeutic interventions such as electrical stimulation and targeted drug delivery to SNr and STN in human patients and experimental animal models of epilepsy, highlighting the opportunities for overcoming pharmacoresistance in epilepsy by investigating these promising target structures.